2012
DOI: 10.1186/1471-2458-12-322
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial on the efficacy of exhaled carbon monoxide measurement in smoking cessation in primary health care

Abstract: BackgroundSmoking cessation is beneficial for our health at any point in life, both in healthy people and in people already suffering from a smoking-related disease. Any help to quit smoking can produce considerable benefits for Public Health. The purpose of the present study is to evaluate the efficacy of the CO-oximetry technique together with brief advice in smoking cessation, in terms of reduction of the number of cigarettes or in the variation of the motivation to quit smoking at month 12 compared with br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
10
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 25 publications
(32 reference statements)
4
10
0
5
Order By: Relevance
“…It corroborates results from other investigations (Ripoll et al. , Chen et al. ) which, in addition, pointed out that exhaled CO measurements may positively influence the success of the smoking cessation through a motivational effect, i.e.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It corroborates results from other investigations (Ripoll et al. , Chen et al. ) which, in addition, pointed out that exhaled CO measurements may positively influence the success of the smoking cessation through a motivational effect, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…This may be due to participant's prior knowledge about the validation of their smoking selfreport status using exhaled CO measurements. It corroborates results from other investigations (Ripoll et al 2012, Chen et al 2013 which, in addition, pointed out that exhaled CO measurements may positively influence the success of the smoking cessation through a motivational effect, i.e. by showing immediately to the patient the harmful consequences of exposure to cigarette smoke.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, exhaled carbon monoxide (COExh) in alveolar after breath‐holding technique is in equilibrium with the concentration of carboxyhemoglobin (COHb) in the blood, which provides a rapid, accurate non‐invasive indirect measure of COHb . A number of cutoff levels ranging from 5–6 ppm depending on study population have been suggested for classification of smokers from nonsmokers , COExh for quitting smoking may produce considerable benefits for public health if proven effective . The hypothesis is that COExh can be suggested that some smokers who manage to quit smoking are more aware of the adverse effects of tobacco or to have had their health seriously compromised .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies in our country have used this model among diabetic smokers patients attended in primary care and to confirm smoking abstinence using cooximetry [18] and another where information gathered by cooximetry is the main element to motivate smokers to quit [19]. …”
Section: Introductionmentioning
confidence: 99%